Harttia absaberi, a new species of loricariid catfish (Siluriformes: Loricariidae: Loricariinae) from the upper rio Paraná basin, Brazil - Oyakawa, Osvaldo Takeshi; Fichberg, Ilana; Langeani, Francisco [UNESP] (Sociedade Brasileira de Ictiologia, 2013)
Uma espécie nova de Harttia, tribo Harttiini, é descrita dos tributários da porção superior da drenagem do rio Paraná. A espécie nova, a menor espécie conhecida do gênero, alcançando até 74,0 mm de comprimento padrão, pode ser diferenciada de suas congêneres pela combinação dos seguintes caracteres: abdômen completamente coberto por placas ósseas, uma única placa preanal, placas da região gular em contato amplo com a placa portadora de canal. Harttia absaberi é a segunda espécie do gênero conhecida da porção superior da drenagem do rio Paraná.

A new species of Harttia, tribe Harttiini, is described from tributaries of upper portions of rio Paraná drainage. The new species, the smallest known species of the genus, attaining up to 74.0 mm of standard length, can be distinguished from its congeners by the combination of the following characters: abdomen completely covered by plates, a single preanal plate, plates of the gular area in broad contact with the canal plate. Harttia absaberi is the second species of the genus known from the upper portion of rio Paraná drainage.
Keywords: Harttiini; Loricarioidea; Neotropical fishes; Ostariophysi; Taxonomy